DESKRIPSI KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DITINJAU DARI MODUL AJAR GURU SISWA KELAS 1 DI SD NEGERI 12 MEMPAWAH HILIR - Ahmad Rohay; Dessy Setyowati; Yuni Istiarini (STKIP Subang, 2025)
This research aims to describe the Strengthening the Pancasila Student Profile Project in view of the Class I Student Teacher Teaching Module at SD Negeri 12 Mempawah Hilir. The project for strengthening the Pancasila student profile (P5) is an effort to encourage the achievement of the Pancasila student profile by using a new paradigm through project-based learning. This research method uses a descriptive qualitative method, with data and data sources obtained using an observation data collection system and analysis of P5 teacher teaching modules on the theme of sustainable lifestyles. The data collection technique used is observation technique. The data source for this research is the P5 class I teaching module at SD Negeri 12 Mempawah Hilir. The results of field observations regarding the Description of Strengthening the Pancasila Student Profile Project Reviewed from the Teaching Module for Grade I Students at SD Negeri 12 Mempawah Hilir, it can be seen that there is a lack of exposure to human activities with their resulting global impacts, including climate change. Lack of exposure to being environmentally friendly and addressing environmental problems, and promoting a sustainable lifestyle. Lack of activities in developing thinking skills to understand the relationship between human activities and their resulting global impacts, including climate change. Lack of instructions regarding activities in building awareness to be environmentally friendly.